Do PFL ao DEM: uma análise das bancadas - Cioccari, Deysi (2016)
This thesis take the Partido da Frente Liberal (PFL) and his successor Democratas (DEM) as exponents of the most striking features of the national party system and political system that emerged in the new constitutional order, which began in 1988. This paper seeks to explain the reasons for the decline of the DEM by analyzing its history and its electoral performance. The thesis assumes that the Democratas articulates political forces in such a way that serves as an example of how Brazilian politics. We understand that the DEM is actually a reflection of a greater crisis, from the growth of the Brazilian conservatism begins to slow reaction signals. Situations throughout its history, as the gateway to the opposition that triggered their weakening and the formation of the party in order to occupy positions in government, are nothing more than a reflection of the crisis of the parties. This thesis seeks to show that even over the thirteen years as opposition, the party maintained its conservative discourse and the search for positions now offers a slow recovery, as is the impeachment of President Dilma Rousseff. We believe that an analysis of the parliamentary fronts, one of the largest Brazilian parliament lobbies, endowed with high financial power and ideological clarity, specifically the Democratas fronts, can explain and exemplify the current Brazilian political model and how to act and always acted the party. We also look at the Parliamentary Group on defense of Evangelicals and Parliamentary Group on defense of the arms industry and Parliamentary Group on defense the agribusiness, three power articulators in Congress which the DEM is part and has expressive voice to demonstrate how to pronounce the parliamentarians